2016
DOI: 10.1177/0363546516660980
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Lateral Ligament Complex Ankle Sprains in National Collegiate Athletic Association Sports

Abstract: LLC sprains were the most commonly reported injury diagnosis among United States collegiate student-athletes. Continued examination of interventions that aim to reduce the incidence, severity, and recurrence of LLC sprains, specifically in women, is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
203
1
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(221 citation statements)
references
References 32 publications
7
203
1
10
Order By: Relevance
“…In the last two decades, numerous studies have been conducted to identify the mechanisms of CAI, substantially studying a single component of sensorimotor impairments (eg, strength, proprioception, postural control, etc) . However, related to common mechanisms of LAS, the injury frequently occurs during jumping, landing, and cutting maneuvers . Because of this, results of most previous studies primarily examining a static measure of sensorimotor impairments may not fully provide dynamic characteristics of altered movement strategies during functional tasks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last two decades, numerous studies have been conducted to identify the mechanisms of CAI, substantially studying a single component of sensorimotor impairments (eg, strength, proprioception, postural control, etc) . However, related to common mechanisms of LAS, the injury frequently occurs during jumping, landing, and cutting maneuvers . Because of this, results of most previous studies primarily examining a static measure of sensorimotor impairments may not fully provide dynamic characteristics of altered movement strategies during functional tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Lateral ankle sprains (LAS) are the most common lower-extremity injury during sport activities. 1 It has been reported that LAS could be associated with reduced proprioception (eg, joint position and force sense errors) 2 and diminished muscular strength and activation (eg, amplitude, timing, and recruitment). 3 Persistent sensorimotor deficits may lead to reorganization of sensorimotor processing in the central nervous system, resulting in altered feedforward motor control following initial and/or recurrent LAS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, preventative measures such as prophylactic ankle supports and postural control training are viable options for LAS prevention, 31,32 and perhaps may be particularly valuable for taller athletes and those with a previous ankle sprain. As a LAS in collegiate women's soccer players occurs through a variety of mechanisms (~35% player contact, ~27% non-contact, ~25% surface contact, ~13% other), 33 postural control training likely should be diversified to include static and dynamic balance exercises, dynamic stability following a landing or cutting task, and external perturbations. Future studies should examine women's soccer players.…”
Section: Discussionmentioning
confidence: 99%
“…Ankle sprains are very common sports injuries but can also happen during daily activities such as walking or even getting out of bed 1, 2 . Patients with inversion ankle sprains constitute a large percentage of these injuries, and occur with an incidence of one sprain per 10,000 people per day 3, 4 .…”
Section: Introductionmentioning
confidence: 99%